Testing of Design Concept HS76A AC Micro-controller for KRL JR205 Series - Ghiffari Taqiyuddin Muhammad (Jurnal Teknik Transportasi, 2025)
The AC (Air Conditioner) system is an important component that must be present on Kereta Rel Listrik (KRL) in accordance with the regulations set by the government regarding minimum service standards. Currently, there are trains that experience damage to the AC micro-controller, causing the AC system to malfunction and making the train unfit for operation. Due to various factors and conditions, the AC micro-controller cannot be repaired, so it is necessary to design a new AC microcontroller that can replace the damaged AC microcontroller. This study aims to design the design concept of the AC microcontroller as an AC system controller with a contactor on the 6-door trailer train KRL JR205 Series. The methodology used in this study includes observation, literature study, document study, system design, testing and analysis of test results. The main components used in this microcontroller system include 24V Omron G2R relay, M7 diode, JST cable and socket, WeAct blackpill STM32F401, PC817 optocoupler, J3Y s8050 transistor, resistor, ATHYC 24C08N PU27 IC, capacitor, and female header. The results of this study indicate that the microcontroller design is able to control the operation of the train's AC system according to the given program function. Keywords : Micro-controller, Air Conditioner, Train